JURIDICAL-NORMATIVE REVIEW OF THE DESIGNATION OF ARMED CRIMINAL GROUPS (KKB) IN PAPUA AS TERRORIST GROUPS - Napang, Marthen; Rohman, Syaiful (Journal of Terrorism Studies, 2021)
There are differences of opinion among various groups after the stipulation of the Armed Criminal Group (KKB) in Papua as a terrorist group/organization. KKB has been identified with the West Papua National Liberation Army (TPNPB-OPM), which is one of the armed separatist movements in Papua. The determination based on armed violence carried out by the KKB has political, ideological, and security motives which are elements in the crime of terrorism. In the context of criminal law reform, the drafters of the Criminal Code separate criminal acts of terrorism and treason in different forms and concepts. Separately, they are categorized as special crimes and crimes against state security. By using the normative juridical method, the authors conclude that the determination of the KKB as a terrorist group/organization is the right policy of the Indonesian government. Based on the three motives above, the KKB can now be categorized as an ethnic-nationalist separatist terrorism group.